Outcome of meniscus surgery at University Malaya Medical Centre - Vinayaga, P.; Amalourde, A.; Tay, Y.G; Chan, K.Y. (Malaysian Medical Association, 2001)
Between January 1994 to December 1998, 133 patients had a meniscal surgery at University Malaya Medical Centre. Fifty-four patients were assessed and scored with the Lysholm and Tegner scoring system. Twenty-nine patients had partial meniscectomies and 25 had meniscus repair. The outcome was successful in 80% with meniscal repair and 51.7% with partial meniscectomy. The outcome of meniscal repair in this study is comparable to other reported series. However, the failure rate for partial meniscectomy was high.